2021
DOI: 10.1002/chem.202100891
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Alloys from Fluorinated Hybrid Tri4Di6Imine Cages

Abstract: To create innovative materials, efficient control and engineering of pore sizes and their characteristics, crystallinity and stability is required. Eight hybrid Tri4Di6 imine cages with a tunable degree of fluorination and one fully fluorinated Tri4Di6 imine cage are investigated. Although the fluorinated and the non‐fluorinated building blocks used herein differ vastly in reactivity, it was possible to gain control over the outcome of the self‐assembly process, by carefully controlling the feed ratio. This re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
(22 reference statements)
0
9
0
1
Order By: Relevance
“…From a design perspective, improving hydrophobicity of the sieving platform can improve the kinetics of hydrocarbon separation. This has been verified in organic cages and MOFs where using fluorine improved not only hydrophobicity but also thermal stability [37–45] . Herein, an adaptive porous fluorinated leaning pillararene was synthesized with persistent porosity and was efficiently employed to separate benzene traces after catalytic hydrogenation to produce high purity cyclohexane under dynamic conditions (Figure 1).…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…From a design perspective, improving hydrophobicity of the sieving platform can improve the kinetics of hydrocarbon separation. This has been verified in organic cages and MOFs where using fluorine improved not only hydrophobicity but also thermal stability [37–45] . Herein, an adaptive porous fluorinated leaning pillararene was synthesized with persistent porosity and was efficiently employed to separate benzene traces after catalytic hydrogenation to produce high purity cyclohexane under dynamic conditions (Figure 1).…”
Section: Figurementioning
confidence: 78%
“…This has been verified in organic cages and MOFs where using fluorine improved not only hydrophobicity but also thermal stability. [37][38][39][40][41][42][43][44][45] Herein, an adaptive porous fluorinated leaning pillararene was synthesized with persistent porosity and was efficiently employed to separate benzene traces after catalytic hydrogenation to produce high purity cyclohexane under dynamic conditions (Figure 1). This fluorinated molecular sieving platform showed a relatively fast adsorption, which was comparable to MOFs with high selectivity and reproducibility.…”
mentioning
confidence: 99%
“…After recrystallization, these cages with unlimited miscibility in the solid‐state were obtained as highly crystalline samples that even retained the crystal lattice, forming alloys. They remained essentially nonporous although huge voids are present in the structure, because they are not interconnected, 0D pores [18] …”
Section: Porous Organic Cagesmentioning
confidence: 99%
“…They remained essentially nonporous although huge voids are present in the structure, because they are not interconnected, 0D pores. [18] A series of three rylene-type cages were investigated by the group of Šolomek, also extending the repertoire of POCs towards photochemistry (Figure 7). [19] The incorporated rylene diimides are not only interesting because of their strong adsorption and emission but they are also potent electron acceptors with favorable redox potentials.…”
mentioning
confidence: 99%
“…13 Alternatively, it was demonstrated that discrete organic cages could be synthesized instead of COFs using different starting materials that induce the 3D geometry. [14][15][16][17] Such cages are commonly porous organic materials. Their synthesis usually employs imine bond formations, based on the reaction between amine and aldehyde components.…”
Section: Introductionmentioning
confidence: 99%